Development of a Minimally Actuated Jumping-Rolling Robot. (29th April 2015) - Ho, Thanhtam; Lee, Sangyoon
This paper presents development of a hybrid mobile robot in order to take advantage of both rolling and jumping locomotion on the ground. According to the unique design of the mechanism, the robot is able to execute both jumping and rolling skilfully by using only one DC motor. Changing the centre of gravity enables rolling of the robot and storage of energy is utilized for jumping. Mechanism design and control logic are validated by computer simulation. Simulation results show that the robot can jump nearly 1.3 times its diameter and roll at the speed of 3.3 times its diameter per second.